Application of the Tek-Press Method to Fluently Read the Al-Quran for Students at the Kyai Syarifuddin Islamic Boarding School in Lumajang - Mochammad Syamsul Arifin (Journal of Islamic Education Research, 2024)
This research examines the application of the tek-press method for fluency in reading the Koran, focusing on the application of the method itself. In this modern era, there are many developments and advances, one of which is that cellphones and televisions have become an option. so that when it comes to reading the Koran, they don't understand it. Someone who reads the Koran poorly must need guidance from someone who can read the Koran well. In carrying out this research, the researcher chose an profitable research method, which in this profitable research method improves or perfects an activity or program implementation. The results of this research show that the tek-tekan method is very helpful for students in learning the knowledge of the Koran.